A Prospective Review on Selectable Marker-Free Genome Engineered Rice: Past, Present and Future Scientific Realm - Singh, Rajveer; Kaur, Navneet; Praba, Umesh Preethi; Kaur, Gurwinder; Tanin, Mohammad Jafar; Kumar, Pankaj; Neelam, Kumari; Sandhu, Jagdeep Singh; Vikal, Yogesh (Frontiers in Genetics, 2022)
Rice being a staple food crop has gained mainstream in genome engineering for its genetic improvement. Genome engineering technologies such as transgenic and genome editing has allowed the significant improvement of target traits in relation to various biotic, abiotic as well as nutrition for which genetic diversity is lacking. In comparison to conventional breeding, genome engineering techniques are more precise and less time consuming. However, one of the major issue in biotech rice commercialization is the utilization of selectable marker genes (SMGs) in the vector construct which when incorporated in the genome are considered to pose risks to human health, environment and biodiversity, and thus become a matter of regulation. The various conventional strategies (co-transformation, transposon, recombinase systems, and MAT-vector) have been used in rice to avoid or remove the SMG from the developed events. However, the major limitations of these methods are; time consuming, left over cryptic sequences in the genome, variable frequency. In contrarily to these methods, CRISPR/Cas9 based marker excision, marker-free targeted gene insertion, programmed self elimination and RNP based delivery enabled us to generate marker free rice engineered plants in more precise and in less time. Although the CRISPR/Cas9 based SMG-free approaches are in their budding stage, further research and their utilization in rice could help to break the regulatory barrier in its commercialization. In the current review we have discussed the limitations of traditional methods followed by advanced techniques. We have also proposed a hypothesis, “DNA free marker less transformation” method to overcome the regulatory barriers posed by SMGs.